Anaesthesia management in Chronic Kidney Disease (CKD) patient undergo repair pseudoaneurysms surgery: a case report - Tan Andi; Tjahya Aryasa; Tjokorda Gde Agung Senapathi (Indonesian Vascular Access Association (IVAA), 2021)
Introduction: Chronic kidney disease (CKD) is marked by the presence of kidney damage (usually defined as estimated GFR < 60 mL/ min/1.73 m2) for 3 or more months, and it may be caused by a multitude of disease processes. Management of patients with CKD includes aggressive treatment of the underlying cause, pharmacologic therapy to delay disease progression and prevent complications, and preparation for hemodialysis as ESRD ensues. Case presentation: In this case report, a 48-year-old man with a pseudoaneurysms due to the insertion of a vascular access for hemodialysis, undergo repair pseudoaneurysms surgery under general anesthesia, at the Sanglah General Hospital, October 2020. The patient came with fully awareness, blood pressure 145/95 mmHg, heart rate 85 times per minute regular and oxygen saturation 97% with room air. Conclusion: General anesthesia in patients with CKD requires an understanding of the pathologic changes that accompany renal disease, co-existing medical conditions, and the impact of reduced renal function on drug pharmacokinetics.